SPECTATOR'S NOTEBOOK: RECEPTION AND REREADING OF A. P. CHEKHOV'S THEATRE IN THE WORK OF GEORGES BANU (Philological Studies, 2025)
The subject of this paper is the reception and rereading of Chekhov's plays, as well as their productions on the contemporary European theatre stages, in the work of the French theatrologist, critic and essayist of Romanian origin, Georges Banu (1943-2023). The paper analyzes in detail his studies and books dedicated to Chekhov's theatre, in which he reinterpretates the works of the Russian playwright in the light of the mutations of the late 20th and early 21st centuries, confirming their relevance to our contemporary world. The paper focuses in particular on the book in which Banu revisits Chekhov's last play, The Cherry Orchard, through its key stagings by major European directors in recent decades, which illuminate various aspects of it. In his reflection, dedicated to Chekhov's testamentary play, Banu compares the demise of the cherry orchard at the threshold of the 20th century with the disappearance that threatens the theatre and the library today, in the era of digital entertainment. The paper focuses on the analysis of the specifics and challenges of theatrical reception and the role of Banu as an "informed/educated spectator" in reconstructing and interpretating the theatrical performance and creating a "living memory" for it. Additionally, this article highlights the contribution of Banu's works in preserving and transmitting the memory of Chekhov's theatre, as well as the theatre of our time. Finally, the paper refers to the personal portrait of Chekhov and his theatre, as sketched by Georges Banu, who reinterprets the Russian playwright as our fellow man, and in whose face we recognize the reflection of the author of the portrait, as well as our own.